Novel Presentation of Terminal Ileitis Associated with Secukinumab Therapy - Aciel Ahmed Shaheen; Ismail Hader; Zakaria Aqel (Case Reports in Gastrointestinal Medicine)
Inflammatory bowel disease (IBD) and psoriasis are chronic inflammatory immune-mediated diseases. The interleukin-23- (IL23-) T helper (Th)17 pathway has been implicated in their pathogenesis, with multiple biologic therapies targeting this pathway. IL-17, the main proinflammatory cytokine produced by (TH)17, has been targeted by antibodies and IL-17 receptor blockers with favorable outcomes in treating psoriasis and psoriatic arthritis. However, their role in IBD is unpredictable as studies reported worsening of IBD with agents targeting IL-17 and rare case reports with new-onset IBD. We present a case of Crohn's-like severe terminal ileitis and worsening diverticulitis complicated by intestinal perforation requiring total parenteral nutrition shortly after being started on secukinumab.